2009
DOI: 10.1159/000183736
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib Induces Therapeutic Response in a Patient with Metastatic Collecting Duct Carcinoma of Kidney

Abstract: Background: Collecting duct carcinoma (CDC) is a rare and aggressive variant of renal cell carcinoma (RCC), which has poor response to cytokine therapy and chemotherapy. Introduction of tyrosine kinase inhibitors (TKIs), in particular sorafenib and sunitinib, is changing the treatment paradigm for management of RCC. However, patients with CDC have been excluded from the majority of randomised trials involving the use of TKIs. Case Report: Our patient with metastatic CDC was treated with sorafenib, and demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 12 publications
(13 reference statements)
0
20
0
Order By: Relevance
“…Miyake et al 37 reported a contribution of sunitinib to a slight decrease in metastatic tumour burden that fell short of a partial response. Finally, Ansari et al 38 reported a response, with minimal side effects, to sorafenib in a patient with metastatic cdc.…”
Section: 24mentioning
confidence: 97%
“…Miyake et al 37 reported a contribution of sunitinib to a slight decrease in metastatic tumour burden that fell short of a partial response. Finally, Ansari et al 38 reported a response, with minimal side effects, to sorafenib in a patient with metastatic cdc.…”
Section: 24mentioning
confidence: 97%
“…Recently, the favorable clinical activity of sunitinib against non-clear cell carcinomas, including papillary and chromophobe carcinomas, has also been reported [8,9]; however, this is the first reported case demonstrating a therapeutic response of metastatic CDC to sunitinib. Furthermore, a recent report presented a case of metastatic CDC showing response to sorafenib [10]. Although the precise molecular mechanism involved in the antitumor activity of multiple tyrosine kinase inhibitors against CDC remains largely unknown, these findings suggest that the efficacy of these agents, for example sunitinib and sorafenib, against metastatic CDC needs to be prospectively evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Although radical surgery is the basic type of therapy and different protocols have been applied, the challenge involves the identification of novel therapeutic modalities (9). no standard protocols have been established for the treatment of CDC.…”
Section: Discussionmentioning
confidence: 99%